The Beethoven Society, having effected an engagement with H. L. Bateman, esq. for the professional services of the unrivaled songstress M'lle Parepa, will give a performance of Handel's grand oratorio, The Messiah, at Allyn Hall, Hartford, on Monday eve'g, December 25th, 1865 - Beethoven Society (Hartford, CT)::::::::::::::: (Hartford, CT; H. S. Griffiths & Bro., printers, 2020)
Christmas-day program sponsored by the Beethoven Society in Hartford, CT, on December 25, 1865, with performance of Handel's Messiah.